Long‐term efficacy of NASHA Dx injection therapy for treatment of fecal incontinence. Issue 8 (19th May 2014) - Mellgren, A.; Matzel, K. E.; Pollack, J.; Hull, T.; Bernstein, M.; Graf, W.; The Nasha Dx Study Group
Abstract Background Injectable bulking treatment for fecal incontinence (FI) is intended to expand tissue in the anal canal and prevent fecal leakage. Use of injectable bulking agents is increasing because it can be performed in an outpatient setting and with low risk for morbidity. This study evaluated the long‐term (36‐month) clinical effectiveness and safety of injection of non‐animal stabilized hyaluronic acid/dextranomer (NASHA Dx) on FI symptoms. Methods In a prospective multicenter trial, 136 patients with FI received the NASHA Dx bulking agent. Treatment success defined as a reduction in number of FI episodes by 50% or more compared with baseline (Responder50). Change from baseline in Cleveland Clinic Florida Fecal Incontinence Score (CCFIS) and Fecal Incontinence Quality of Life Scale (FIQL), and adverse events were also evaluated. Key Results Successful decrease in symptoms was achieved in 52% of patients at 6 months and this was sustained at 12 months (57%) and 36 months (52%). Mean CCFIS decreased from 14 at baseline to 11 at 36 months (p < 0.001). Quality‐of‐life scores for all four domains improved significantly between baseline and 36 months of follow‐up. Severe adverse events were rare and most adverse events were transient and pertained to minor bleeding and pain or discomfort. Conclusions & Inferences Submucosal injection of NASHA Dx provided a significant improvement of FI symptoms in a majority of patients and this effect was stable during the course of the follow‐up and maintained for 3 years.